Inflammation, Infection and Preterm Birth - Burdet, Juliana; Paula Dominguez Rubio, Ana; Ines Salazar, Ana; Laura Ribeiro, Maria; Ibarra, Cristina; Maria Franchi, Ana (Current Pharmaceutical Design, 2014)
Preterm birth is the leading cause of perinatal morbidity and mortality. Pathological processes that have been linked with preterm birth infection and / or intrauterine inflammation are most frequently found associated with their induction. Studies in animal models and human research showed prior infections to the induction of labor, the anteriority of infection over labor induction, and the existence of a subclinical latency phase between these two phenomena. The ascending route from the vagina and the cervix is preponderant but also microorganisms may access the amniotic cavity and the fetus by other pathways. During inflammation associated to infection, Prostaglandins are released simultaneously with Nitric oxide and their overproduction could be detrimental. Prostaglandins promote uterine contractions contributing to embryonic and fetal expulsion. Therefore aberrant activation of the inflammatory response may cause premature labor and this does not seem to depend on how the microoorganisms accessed the uterus.
Keywords: Pregnancy- preterm labor- infection- inflammation